1989
DOI: 10.1177/37.7.2732461
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenous distribution of free calcium and propagation of calcium transient in gastric parietal cells revealed by digital imaging microscopy.

Abstract: Spatial and temporal changes of cytoplasmic free calcium concentration ([Ca2+]i) in single parietal cells of guinea pig were investigated with a digital imaging microscope equipped with a microspectrofluorometer, using a Ca2+-sensitive dye, fura-2. Intracellular distribution of [Ca2+]i was not homogeneous, but there were two kinds of [Ca2+]i gradient in the resting parietal cells, one a continuous gradient increasing towards the plasma membrane and a second discontinuous gradient (Ca2+ plateau) in some restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

1990
1990
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…These results are in agreement with a previous report [41], which showed that Ins(1,4,5)P3 can partially release Ca2+ from intracellular Ca2+ stores in permeabilized parietal cells. Moreover, Tsunoda et al [43] demonstrated that in parietal cells gastrin can induce Ca2+ waves propagating within the cytosol, consistent with the existence of two different Ca2+ stores in this cell type.…”
Section: Gastrin Receptor and Muscarinic Receptor Regulate Common Ca2mentioning
confidence: 69%
“…These results are in agreement with a previous report [41], which showed that Ins(1,4,5)P3 can partially release Ca2+ from intracellular Ca2+ stores in permeabilized parietal cells. Moreover, Tsunoda et al [43] demonstrated that in parietal cells gastrin can induce Ca2+ waves propagating within the cytosol, consistent with the existence of two different Ca2+ stores in this cell type.…”
Section: Gastrin Receptor and Muscarinic Receptor Regulate Common Ca2mentioning
confidence: 69%
“…6A). It is concluded that these currents were activated by a rise in the cytosolic free Ca 2+ concentration ([Ca2+]i); because (i) using fura-2 CCh has been shown to increase [Ca2+]i in parietal cells of a variety of animal species (Chew & Brown, 1986;Negulescu & Machen, 1988;Black et al, 1989;, including the guinea pig (Tsunoda et al, 1989; H. Tatsuta, S. Ueda & Y.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it appears that CCh induced activation of K + currents as well as nonspecific cation currents. Cytosolic Ca 2+ is known to be increased by CCh in guinea pig parietal cells (Tsunoda, Yodozawa & Tashiro, 1989). Therefore, cytosolic Ca 2+ rises may be causatively involved in CCh-induced responses.…”
Section: Calcium-activated Potassium Currents and Nonselective Cationmentioning
confidence: 99%
“…It has been reported previously that the intracellular distribution of calcium-binding proteins may alter during development [parvalbumin (Braun et al, 1986)] or after vitamin D administration [calbindin (Taylor and Inpanbutr, 1988)l. A spatially heterogeneous subcellular distribution was also found for both free and total calcium (Chandra et al, 1989;Tsunoda et al, 1989). Tank et al (1988) were able to monitor the distributed Ca" concentration in single cerebellar Purkinje cells in a slice preparation.…”
Section: Immunohistochemical and In Situ Hybridization Studiesmentioning
confidence: 93%